Using composite measures in police cynicism research: An application of canonical factor regression - Regoli, Bob (Journal of quantitative criminology, 1991)
In this paper, a “new” analytical strategy, the canonical factor regression method (CFRM) is introduced as a tool for constructing indices and measuring reliabilities of those indices from items derived from Niederhoffer's police cynicism index. Data for the project were derived from the survey responses of 574 Illinois police chiefs. Analysis of the data in the present project suggests that CFRM is a useful tool for constructing composite indices. CFRM allowed us to provide a more powerful test of hypothesized relationships between dimensions of cynicism and theoretically salient predictor variables than has previously been possible.